Evidence based recommendations on feedback practice: A systematic literature review - Dello Russo, S.; Mirfakhar, A. S.; Miraglia, M. (Academy of Management Annual Meeting Proceedings 2021, 2021)
Literature on feedback, and particularly feedback quality, has burgeoned over the past quarter century. This is especially relevant for practitioners who are turning to feedback as a remedy and solution to improve performance management. Within this scope, we aimed to uncover how research can best assist practice on feedback and contribute to rigorous, evidence-based management. To this aim we conducted a systematic literature review of the practical implications contained in feedback studies. Our pool of retained articles (N=120) allowed us to shed light on several aspects, namely why recommendations are offered, what recommendations are endorsed, when and where the recommendations are most applicable, to whom those are addressed, and how they are framed by researchers. Based on our findings, we summarize the main practical implications on feedback that scientific research has to offer to practitioners; highlight areas where research is still needed and derive an agenda for future feedback studies; offer recommendations to researchers on how to pay attention, craft and enrich their practical implications sections.